ANALISA LIMBAH RUMAH TANGGA TERHADAP DAMPAK PENCEMARAN LINGKUNGAN - NI MADE NIA BUNGA SURYA DEWI (Universitas Mahasaraswati K. Mataram, 2021)
What is not included in the waste originating from daily activities in household life is feces and specific waste (requires special management/ B3 waste). The impact of household waste can affect environmental pollution such as reducing water quality which will result in the level of health of living things and the environment. As for this, it has been stated in the government regulation of the Republic of Indonesia Number 81 of 2012 concerning the Management of Household Waste and Similar Household Waste.The lack of concern for the household environment itself, the lack of garbage disposal sites and the lack of firmness in law enforcement for violators are some of the obstacles that occur in the community in managing household waste. There are several ways of planning and managing household waste that can be done, such as by doing recycling, burning, separating, composting and decaying waste.